A molecular marker for the identification of Simulium squamosum (Diptera: Simuliidae) - Mank, R.; Wilson, M.D.; Rubio, J.M.; Post, R.J. (Annals of Tropical Medicine and Parasitology, 2004)
All except one of the important groups of West African vectors of Onchocerca volvulus that lie within the Simulium damnosum complex can be distinguished from each other using morphological characteristics. The exception is S. squamosum, which overlaps with other species, and this results in significant levels of misidentification. Variation in the untranscribed H3-H4 histone intergenic spacer region of flies of the 5. damnosum complex has now been investigated. Although a CAA/CAG microsatellite was found to be hyper-variable and unsuitable for species diagnosis, a 10-bp indel seemed to vary in a species-specific manner. This indel was apparently absent from S. squamosum but present in all of the other species tested (S. damnosum s.s., S. sirbanum, S yahense, S. sanctipauli and 5. leonensel konkourense). It should now be possible to identify individual, adult, female S. squamosum from the absence of the indel, using a PCR-based amplification and agarose- or polyacrylamide-gel electrophoresis, thus removing the major barrier to the routine identification of unknown samples.